Social Competence and Its Related Factors in High School Students: A Cross-sectional Study - Fatemeh Hosseinzadeh Siboni; Abdolhosein Emami Sigaroudi; Moluk Pouralizadeh; Saman Maroufizadeh (Journal of Holistic Nursing and Midwifery)
Introduction: Social competence can help adolescents achieve effective social interactions and establish and maintain successful relationships with peers and society.